Combined cereal and pulse flavonoids show enhanced bioavailability by downregulating phase II metabolism and ABC membrane transporter function in Caco-2 model. (1st May 2019) - Ravisankar, Shreeya; Agah, Shima; Kim, Hyemee; Talcott, Susanne; Wu, Chaodong; Awika, Joseph
Highlights: Cereals and pulses are complementary dietary commodities. Cereals and pulse flavonoids are structurally different. Combined cereal flavones and pulse flavonols show enhanced absorption. Effect due to suppression of phase II metabolism and ABC transporter function. Strategic combinations of cereal and pulses could enhance biological benefits. Abstract: Predominant flavonoids in cereals and pulses are structurally different and may positively interact to enhance bioactivity in combined diet. This work investigated the effects of combined cereal 3-deoxyflavonoids (apigenin, naringenin) and pulse flavonols (quercetin), along with natural extracts, on their bioavailability and underlying mechanisms using Caco-2 monolayer model. Membrane permeability, phase II metabolism, and ATP binding cassette (ABC) membrane transporter expression and function were measured. Apparent absorption of quercetin and apigenin increased ( p  < 0.05) 3.3× and 1.5×, respectively, while both compounds were significantly less metabolized in combined treatments. Combinations with naringenin had insignificant effect, suggesting a role for flavonoid C2C3 conjugation. Both natural extracts and apigenin-quercetin combinations synergistically (3–40 fold) downregulated ABC transporter expression, and inhibited P-glycoprotein activity, suggesting direct binding and inhibition of ATPase. Combination of conjugated cereal and pulse flavonoids enhances their potential bioavailability through synergistic inhibition of membrane transporter and phase II enzyme function.